Reconstructing EBV reactivation and DNA damage response kinetics in morphologic pseudotime - Dina G. Tekle; Craig J. Dobry; Jonathan Z. Sexton; Elliott D. SoRelle (Proceedings of the National Academy of Sciences, 2026)
Epstein–Barr virus (EBV) lytic infection contributes to oncogenesis and autoimmunity and depends on subversion of host DNA damage responses (DDR). We used high-content screening (HCS) to systematically capture single-cell morphologic profiles and pseudotemporal dynamics of EBV reactivation and DDR across common B cell models and lytic induction treatments. We generated an atlas (>850,000 cells) of spatiotemporally distinct phenotypes of immediate-early and late lytic proteins, viral and cellular DNA replication, and double-stranded break (DSB) DDR factors. Cell segmentation, feature quantification, and clustering identified treatment- and model-dependent cell responses and lytic induction. Lytic and latent cells showed distinct genotoxin-induced DDR profiles, and lytic protein localization varied by pharmacologic and physiologic stimuli. Pseudotime trajectories revealed viral replication compartment (VRC) nucleation and expansion alongside concomitant DDR localization. The early DDR marker γH2AX was depleted from VRCs but widespread across host chromatin throughout reactivation. Surprisingly, the lytic-essential late DDR protein 53BP1 was present prior to viral genome replication but subsequently undetected in VRCs and host chromatin, indicating spatial and kinetic DDR dysregulation during EBV reactivation. These data support a model wherein EBV transiently employs host DSB DDR mediators to initiate genome replication while host-targeted DDR is initiated but impaired. We further show biological generalizability and utility of our method across microscope systems. HCS paired with morphologic pseudotime analysis thus provides a powerful approach to recover single-cell host–virus dynamics from snapshot samples.